A Multi-Method Approach for Impact Assessment of Some Heavy Metals on Lactuca sativa L. - Maria-Loredana Soran; Aura Nicoleta Sîrb; Ildiko Lung; Ocsana Opriş; Otilia Culicov; Adina Stegarescu; Pavel Nekhoroshkov; Delia-Maria Gligor (Molecules, 2023)
Heavy metals represent a large category of pollutants. Heavy metals are the focus of researchers around the world, mainly due to their harmful effects on plants. In this paper, the influence of copper, cadmium, manganese, nickel, zinc and lead, present in soil in different concentrations (below the permissible limit, the maximum permissible concentration and a concentration higher than the maximum permissible limit) on lettuce (Lactuca sativa L.) was evaluated. For this purpose, the authors analyzed the variation of photosynthetic pigments, total polyphenols, antioxidant activity and the elemental content in the studied plants. The experimental results showed that the variation of the content of biologically active compounds, elemental content and the antioxidant activity in the plants grown in contaminated soil, compared to the control plants, depends on the type and concentration of the metal added to the soil. The biggest decrease was recorded for plants grown in soil treated with Ni I (−42.38%) for chlorophyll a, Zn II (−32.92%) for chlorophyll b, Ni I (−40.46%) for carotenoids, Pb I (−40.95%) for polyphenols and Cu III (−29.42%) for DPPH. On the other hand, the largest increase regarding the amount of biologically active compounds was registered for Mn I (88.24%) in the case of the chlorophyll a, Mn I (65.56%) for chlorophyll b, Pb I (116.03%) for carotenoids, Ni III (1351.23%) for polyphenols and Ni III (1149.35%) for DPPH.